2021
DOI: 10.1007/s13563-021-00272-5
|View full text |Cite
|
Sign up to set email alerts
|

Unbridled coal extraction and concerns for livelihood: evidences from Odisha, India

Abstract: Coal mining and its unfavourable consequences have generated global attention. It has further stimulated the paradoxical debate of development and desolation in the contemporary scenario. Since the coal resources are profusely available in India and it is comparatively less expensive, the country has been largely relying on it for its essential and non-essential consumption needs. Coal resources indirectly fulfil many of the modern requirements and comforts. Consequently, mining of minerals in general and coal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Therefore, the results confirm Ogbonna's views [44] that although coal mining brings wealth to communities, it also destroys the environment. In a study by Paltasingh et al, (2023) [45] it was shown that coal mining brings economic benefits, but it can endanger the health of the environment, humans, and society [45]. In a study by De Valck et al, (2021) it was shown that environmental protection has more economic effects than coal mining because in the long term, coal mining can destroy the climate of a region and destroy local communities [46].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results confirm Ogbonna's views [44] that although coal mining brings wealth to communities, it also destroys the environment. In a study by Paltasingh et al, (2023) [45] it was shown that coal mining brings economic benefits, but it can endanger the health of the environment, humans, and society [45]. In a study by De Valck et al, (2021) it was shown that environmental protection has more economic effects than coal mining because in the long term, coal mining can destroy the climate of a region and destroy local communities [46].…”
Section: Discussionmentioning
confidence: 99%
“…The following literature focuses on the impact of mining on the environment and local livelihoods in general and coal mining in particular. Paltasingh and Satapathy (2021) tried to show the negative effects of coal mining activities. It has a detrimental effect on different sources of livelihoods.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The country has undertaken development efforts over the past years to alleviate diverse socioeconomic difficulties (The NITI Aayog, 2017). 1 However, with the passage of time several emerging challenges like rising population explosion, environmental deterioration, loss of flora and fauna, climate change, social tension and conflicts, growing urbanization and pollution, health hazard, speedy depletion of natural resources, increasing disparity, and lagging human development indices have become perceptible (Kumi et al, 2014; Paltasingh & Satapathy, 2021). The adoption of SDGs provided a definite roadmap to systematically overcome the emerging concerns.…”
Section: Sdgs As Global Development Agendamentioning
confidence: 99%